Pathological and genomic phenotype of second neuroendocrine carcinoma during long-term follow-up after radical radiotherapy for nasopharyngeal carcinoma - Ying-peng Peng; Qiao-dan Liu; Yu-jing Lin; Shun-li Peng; Rong Wang; Xi-wei Xu; Wei Wei; Gui-hua Zhong; Yu-ling Zhou; Ya-qin Zhang; Ye Liu; Si-yang Wang; et al. (Radiation Oncology, 2021)
Abstract Background Second head and neck neuroendocrine carcinoma (NEC) after radical radiotherapy for nasopharyngeal carcinoma (NPC) treatment is rarely reported. The prognosis of second cancer is poor, and our research focuses on finding a breakthrough in the treatment. In this study, we aimed to investigate clinicopathological characteristics and to identify the genomic landscape of second head and neck NECs. Methods We collected five second head and neck NEC cases in the recent three years from our patient database. Clinicopathological data and images were obtained. Genomic analysis was performed using high-throughput second generation sequencing. KEGG pathway enrichment analyses between high-frequency mutations were performed using the STRING database. Results All patients had been diagnosed with second NEC, according to the pathological observations. The interval between diagnosis of NPC and NEC ranged from 10 to 18 years. Two patients had brain or liver metastasis at three and nine months, respectively, after the diagnosis of NEC. Three patients died of the disease with the overall survival time ranging from three to nine months. Commonly altered genes (50%) in second head and neck NECs included TP53, RB1, NOTCH2, PTEN, POLG, KMT2C, U2AF1, EPPK1, ELAC2, DAXX, COL22A1, and ABL1. Those genetic lesions might affect p53 signaling, MAPK signaling, PI3K-Akt signaling, sphingolipid signaling, and neurotrophin signaling pathways. Conclusions Second head and neck NECs had poor prognosis. We revealed, for the first time, the mutational landscape, high-frequency somatic mutations, and potential signaling pathways of second head and neck NECs. Its optimal treatment model needs to be further studied in future clinical trials.